Avaliação da elevação de seio maxilar com instalação imediata de implantes: ensaio clínico prospectivo - Paiva, Luis Gustavo Jaime (2016)
A prospective clinical study of maxillary sinus lift procedures in the posterior region of the maxilla, using only blood clot as filling material, was conducted. Thirteen patients underwent a maxillary sinus lift procedure; 17 maxillary sinus regions were operated on and a total of 34 implants were placed. The sinus mucosa was lifted together with the anterior wall of the osteotomized maxilla and supported by the implants placed. Computed tomography (CT) scans were obtained preoperatively (Tinitial) and 6 months postoperative (T2) for the measurement of bone height and bone volume. Only one implant was lost during 25 months of mean follow-up (97% success). The bone height increase between Tinitial and T2 was 4,12mm; bone volume increases 451,82 mm3 during the same period. Thus, the maxillary sinus lift technique with immediate implant placement, filling with blood clot only, may be performed with a high success rate. No extra costs for biomaterial or morbidity for bone harvesting were necessary.